Megalencephaly-capillary malformation polymicrogyria: A review and complex pediatric case report. Issue 4 (2nd October 2017) - Loughan, Ashlee R.; Harrell, Murphy; Perna, Robert; Allen, Aislyn; Suddarth, Brian
ABSTRACT: Megalencephaly-Capillary Malformation Polymicrogyria (M-CAP) is a rare genetic disorder characterized by a spectrum of anomalies including macrocephaly and neurovascular malformations. Although developmental delays have been identified, research is devoid of neuropsychological data. This case report presents the neuropsychological profile of a 7-year-old, identified with M-CAP. Neuropsychological evaluation was completed subsequent to medical diagnosis. Reports from both parents and teachers included cognitive regression; specifically in the recall of learned material, reading, and information sequencing. Direct testing revealed a WISC-IV GAI at <1 st percentile, a diverse range of scores across the battery, and a splinter skill strength of average to above on visual memory tests. Performance included below grade level reading and writing, reduced adaptive functioning, and reported executive dysfunction. Her strong visual memory skills were recommended as a medium to enhance learning. Neurocognitive deficits revealed diverse, multisystem and multifocal impairments. The neuropsychological evaluation also showed significant decline from the previous evaluation and prompted a neurologic consult and corrective surgical procedure.